Behavior of I4 σ(4c–6e) in tellurolane system and related species, elucidated by QTAIM dual functional analysis with QC calculations. Issue 5 (17th December 2018) - Hayashi, Satoko; Nishide, Taro; Nakanishi, Waro
Abstract: The nature of the A I‐* ‐ A I and A I‐* ‐ B I interactions in B I‐* ‐ A I‐* ‐ A I‐* ‐ B I of I4 σ(4c–6e) in the tellurolane system, C4 H8 (I)Te–I···I–I···I–Te(I)C4 H8 (1 ), and the models is elucidated with QTAIM dual functional analysis (QTAIM‐DFA). Asterisks (* ) are employed to emphasize the existence of bond critical points (BCPs) on the interactions in question. Data from the fully optimized structures correspond to the static nature. Data from the perturbed structures around the fully optimized ones with the fully optimized structures represent the dynamic nature of interactions in QTAIM‐DFA. The A I‐* ‐ A I and A I‐* ‐ B I interactions in the optimized structure of1 ( C i )calcd are predicted to have the Cov‐w (weak covalent) nature appeared in the shared shell region and the t ‐HBwc (typical hydrogen bonds with covalency) nature appeared in the regular closed shell ( r ‐CS) region, respectively. However, both A I‐* ‐ A I and A I‐* ‐ B I interactions in the observed structure in crystals (1 ( C i )obsd ) appear in the r ‐CS region. The isolated structure of only one molecule in vacuum for1 ( C i )calcd vs that surrounded by the same molecules for1 ( C i )obsd arises the different results. The nature of A I‐* ‐ A I and A I‐* ‐ B I in B I‐* ‐ A I‐* ‐ A I‐* ‐ B I of I4 σ(4c–6e) for the models is similarly analyzed.